Airwave oscillometry and spirometry in children with asthma or wheeze - Gunawardana, Shannon; Tuazon, Mark; Wheatley, Lorna; Cook, James; Harris, Christopher; Greenough, Anne (The Journal of asthma, 2023)
Lung function testing is used in diagnosing asthma and assessing asthma control. Spirometry is most commonly used, but younger children can find performing this test challenging. Non-volitional tests such as airwave oscillometry (AOS) may be helpful in that population. We compared the success of spirometry and AOS in assessing bronchodilator responsiveness in children. AOS was conducted alongside routine lung function testing. Resistance at 5 Hz (R5), the difference between the resistance at 5 and 20 Hz (R5-20) and the area under the reactance curve (AX) were assessed. Patients between 5 and 16 years old attending clinic with wheeze or asthma were assessed. Patients performed AOS, followed by spirometry and were then given 400 µg salbutamol; the tests were repeated 15 minutes later. Lung function testing was performed in 47 children of whom 46 (98%) and 32 (68%) performed acceptable baseline oscillometry and spirometry, respectively (p < 0.001). Children unable to perform acceptable spirometry were younger (7.35, range: 5.4-10.3 years) than those who could (10.4, range: 5.5-16.9 years), p < 0.001. The baseline z-scores of AOS R5 correlated with FEV 1 (r = 0.499, p = 0.004), FEF 75 (r = 0.617, p < 0.001), and FEV 1 /FVC (r = 0.618, p < 0.001). There was a positive bronchodilator response assessed by spirometry (change in FEV 1 ≥ 12%) in eight children which corresponded to a change in R5 of 36% (range: 30%-50%) and a change in X5 of 39% (range: 15%-54%). Oscillometry is a useful adjunct to spirometry in assessing young asthmatic children's lung function. The degree of airway obstruction, however, might affect the comparability of the results of the two techniques.